The Lumbee Indians : An American Struggle - Lowery, Malinda Maynor (Book collections on Project MUSE., 2018)
"As the largest tribe east of the Mississippi and the ninth largest in the country, the Lumbees have survived in their original homelands, maintaining a distinct identity as Indians in a bi-racial South. In a work both concise and expansive, Lumbee historian Malinda Maynor Lowery tells this story of survival with a breakthrough approach to rigorous scholarship and personal storytelling. The Lumbees' journey sheds new light on America's defining moments, from the first encounters with Europeans to the present day. How and why did the Lumbees fight to establish and resist the United States? How have they not just survived, but thrived, through Civil War, Jim Crow, the Civil Rights movement, and the War on Drugs, to ultimately establish their own constitutional government in the twenty-first century? Their fight for full federal acknowledgement continues to this day, while the Lumbee people's struggle for justice and determination continues to transform our view of the American experience"--